The Effect Spouse Support And Mental Attitude On The Trade-Fish Economic Recovery - Yuli Purbaningsih; Ahmad Tarmizi Abd Karim; Muhammad Fath Azzajjad; Hasan Djidu; Andri Estining Sejati (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The aim of this research was to measure the effect of partner support and mental attitude on the economic recovery of salted fish traders in the Lamekongga traditional market. This research was an ex-post facto causal associative. The subjects of this research were 19 sellers of salted fish in the Lamekongga traditional market. Data was collected by distributing questionnaires and documentation. Data were analyzed using simple regression and multiple regressions. The results of this research indicate that there is an effect of partner support on economic recovery, mental attitude on economic recovery, then partner support and mental attitude together on the economic recovery of salted fish traders in the Lamekongga traditional market. The effect is positive and significant. The implication of the research is to describe the post-recovery economy, the peak of COVID-19.